Technological Advances in Multiscale Analysis of Single Cells in Biomedicine. Issue 11 (11th September 2019) - Loo, Jacky Fong‐Chuen; Ho, Ho Pui; Kong, Siu Kai; Wang, Tza‐Huei; Ho, Yi‐Ping
Abstract: Single‐cell analysis has recently received significant attention in biomedicine. With the advances in super‐resolution microscopy, fluorescence labeling, and nanoscale biosensing, new information may be obtained for the design of cancer diagnosis and therapeutic interventions. The discovery of cellular heterogeneity further stresses the importance of single‐cell analysis to improve our understanding of disease mechanism and to develop new strategies for disease treatment. To this end, many studies are exploited at the single‐cell level for high throughput, highly parallel, and quantitative analysis. Technically, microfluidics are also designed to facilitate single‐cell isolation and enrichment for downstream detection and manipulation in a robust, sensitive, and automated manner. Further achievements are made possible by consolidating optically label‐free, electrical, and molecular sensing techniques. Moreover, these technologies are coupled with computing algorithms for high throughput and automated quantitative analysis with a short turnaround time. To reflect on how the technological developments have advanced single‐cell analysis, this mini‐review is aimed to offer readers an introduction to single‐cell analysis with a brief historical development and the recent progresses that have enabled multiscale analysis of single‐cells in the last decade. The challenges and future trends are also discussed with the view to inspire forthcoming technical developments. Abstract : Traditional single cell analysis focuses on the investigation of individual cells as a whole at a particular condition due to either the insufficient resolution or the slow processing speed of the available techniques. Modern technological advancements have enabled multiscale analysis of single cells, where cellular heterogeneity may be assessed in a multidimensional and/or multiparameter manner.